Flexible Wearable Sensors for Cardiovascular Health Monitoring. Issue 17 (6th May 2021) - Chen, Shuwen; Qi, Jiaming; Fan, Shicheng; Qiao, Zheng; Yeo, Joo Chuan; Lim, Chwee Teck
Abstract: Cardiovascular diseases account for the highest mortality globally, but recent advances in wearable technologies may potentially change how these illnesses are diagnosed and managed. In particular, continuous monitoring of cardiovascular vital signs for early intervention is highly desired. To this end, flexible wearable sensors that can be comfortably worn over long durations are gaining significant attention. In this review, advanced flexible wearable sensors for monitoring cardiovascular vital signals are outlined and discussed. Specifically, the functional materials, configurations, mechanisms, and recent advances of these flexible sensors for heart rate, blood pressure, blood oxygen saturation, and blood glucose monitoring are highlighted. Different mechanisms in bioelectric, mechano‐electric, optoelectric, and ultrasonic wearable sensors are presented to monitor cardiovascular vital signs from different body locations. Present challenges, possible strategies, and future directions of these wearable sensors are also discussed. With rapid development, these flexible wearable sensors will potentially be applicable for both medical diagnosis and daily healthcare use in tackling cardiovascular diseases. Abstract : Wearable sensors for continuous cardiovascular vital signs monitoring can play an important role in better health management. This review highlights recent advances in materials, configurations, and techniques for heart rate, blood pressure, blood oxygen saturation, and blood glucose monitoring based on wearable sensors using bioelectric, mechanoelectric, optoelectric, and ultrasonic mechanisms. Present challenges and opportunities for these sensors are also discussed.